Pengaruh Gaya Kepemimpinan Situasional Kepala Sekolah dan Budaya Kerja terhadap Kinerja Guru - Bradley Setiyadi; Inirwana Inirwana (SAP (Susunan Artikel Pendidikan), 2022)
This study aims to determine the effect of Principal Situational Leadership Style and Work Culture on Teacher Performance at SMK Negeri 3 Kota Jambi and is expected to provide a solution to the efforts that will be made to improve teacher performance in order to achieve school goals. This study held in the Odd Semester of the 2021/2022 Academic Year, using quantitative research methods with a survey research design. The population in this study were teachers at SMK Negeri 3 Kota Jambi. The sampling technique in this study was using simple random sampling, with a sample of 57 teachers. The results in this study were: (1) There was an effect of the principal's situational leadership style on teacher performance. This can be proven through the results of the t-test where the tcount value was greater than the ttable value, namely 3,120 > 2,004, with a percentage of 39,3%. (2) There was an influence of work culture on teacher performance. This can be proven through the results of the t-test where the tcount value was greater than the ttable value, namely 4,537> 2,004, with a percentage of 27,2%. (3) There was an influence of the principal's situational leadership style and work culture on teacher performance. It showed a significant level of 14,707 while the Ftable value is 3,18, with a percentage of 66.5%, the remaining i.e., i.e. 33,5% is influenced by other factors that were not investigated in this study, such as work stress, job satisfaction and teacher work motivation. From these results, it can be concluded that there is an influence of the principal's situational leadership and work culture on the performance of teachers at SMK Negeri 3 Kota Jambi.